Advancing the Scholarship of Teaching and Learning using Learning Theories and Reflectivity - Lester Brian Shawa (Center for Educational Policy Studies Journal)
The Scholarship of Teaching and Learning (SoTL) remains a mostly elusive notion. For universities to genuinely contribute to SoTL, they must delineate clear parameters of engagement. For example, while some engage SoTL at the academic level, others examine it from an institutional policy perspective. Others view it from national and international frameworks that impact teaching and learning in universities. Engaging SoTL at the academic level, this article uses a postgraduate diploma module, Higher Education Context and Policy (mostly attended by university academics from South African universities) to show how a facilitator could draw from learning theories and reflectivity to teach and advance SoTL. More specifically, it demonstrates how a facilitator could mediate the module utilising a social constructivist learning theory perspective.